Analysis of the presidential election system in Peru - Velarde Koechlin, Carmen Milagros (2020)
This paper analyzes the current system of presidential elections in Peru, adopted by the1979 Political Constitution and kept by the 1993 Political Constitution. It highlights that the establishment of the presidential system through an absolute majority of votes two-round election has affected democracy, preventing its from developing based on the values of social capital. Presidentialism has become personalism, leading to the Parliament losing power and affecting the stability of political parties.